دور نماذج صفوف الانتظار في رفع مستوى جودة الخدمة الصحية في قسم الاستعجالات الطبية بمستشفى طب العيون، ولاية بشار – الجزائر - بلقايد, ثورية; بودية, بشير (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى تقليص زمن انتظار المرضى الذين ينتظرون دورهم لتلقي العلاج في قسم الاستعجالات الطبية بالمؤسسة العمومية الاستشفائية لطب العيون بولاية بشار، والذي يعد عاملا مهم في تقييم جودة الخدمة الصحية المقدمة، وزمن الانتظار الأقل له أثر إيجابيي على رضا المرضى، وتخفيف الضغط على مقدمي الخدمة. وقد توصلت الدراسة من خلال تطبيق نظرية صفوف الانتظار إلى تحديد التوزيع الذي يتبعه كل من معـدل الوصـول ومعـدل الخدمة وتقديم نموذج بديل بإضافة مركز خدمة ثالث إلى المركزين الموجودين في القسم قيد الدراسة، حيث أدى هذا البديل إلى تحسين جميع مؤشرات الأداء، حيث انخفض وقت الانتظار من 33,22 دقيقة إلى 1,721دقيقة، وعدد المرضى في صف الانتظار من 12 مريض إلى 0.62 مريض. Abstract: This study aims to reduce the time patients wait for their turn to receive treatment in the Medical Emergency Department of the General Hospital Institution of Ophthalmology in Bechar province. The patients waiting time is an important factor in evaluating the quality of the health service provided. The less waiting time has a positive impact on the patient satisfaction, and relieves pressure on the service providers. The study, through the application of the waiting queue theory, to determine the distribution of both the Access rate, Service rate and presents an alternative model adding a third service center to the two centers in the department under study. The provided alternative led to the improvement of all performance indicators, as the waiting time has decreased from 33.22 minutes to 1,721 minutes, and the number of patients in the queuing from 12 patients to 0.62 patients
Keywords: جودة الخدمة، الخدمة الصحية، صف الانتظار، معدل الوصول، معدل الخدمة.